Pengaruh Latihan Otot Pernafasan terhadap Peningkatan Fungsi Paru pada Periode Awal Ekstubasi - Setiyawan Setiyawan; Muhamad Nur Rahmad; Noviana Nur Zaidah (Universitas Faletehan, 2024)
There had been no structured breathing exercise intervention for patients at the beginning of post-extubation after the installation of mechanical ventilation in a hospital in Indonesia. Thus, this study aimed to determine the effects of respiratory muscle exercises on lung function in the early period of extubation. The research design used quasi experimental without control group. Respiratory muscle training intervention is carried out 1 hour after extubation through deep breathing 30 times (rest pause for 10 deep breaths) for 30-60 minutes. The exercises were given once a day for 3 days or according to the patient's condition. The population of this study were all patients after installation of a ventilator at the ICU. The sampling technique was consecutive with a total of 30 respondents. The instrument was an observation sheet, the results of respiratory frequency, and oxygen saturation parameters from the bedside monitor. Bivariate data analysis used Wilcoxson test. The results of the study showed that there were effects of respiratory muscle training on lung function in the initial extubation period with a p-value of 0.000 (p-value < 0.05). The results of the study proved that respiratory muscle training can improve the oxygenation function of the lungs in the early period of extubation.